Систематические ошибки измерения концентрации электронов в ионосфере методом фарадеевского вращения и способ их компенсации - Скворцов, Тарас Александрович; Емельянов, Леонид Яковлевич; Фисун, Андрей Васильевич (НТУ "ХПИ", 2015)
Рассматривается способ измерения концентрации электронов в ионосфере радарами некогерентного рассеяния с использованием эффекта Фарадея. Исследуются систематические ошибки измерения, которые возникают из-за неточной поляризационной настройки приемной антенны. Получена формула для оценки указанных ошибок и предложен способ, который позволяет их скомпенсировать даже при неточной поляризационной настройке. Способ позволяет также контролировать точность поляризационной настройки приемной антенны.

The technique of measurement of the ionosphere electron density by incoherent scatter radars with the use of Faraday Effect is considered. Bias errors of electron density measurement that arise because of the inexact polarization adjustment of receiving antenna are studied. A formula for the estimation of the referred errors is obtained. The method for compensating these errors is offered. The method allows obtaining good estimation of the electron density even if polarization adjustment of the antenna is not accurate. The method allows also to control accuracy of the polarization adjustment of receiving antenna. The results of numerical simulation and experimental results obtained by incoherent scatter radar of Institute of Ionosphere (Kharkiv) are presented.
Bias errors of the ionospheric electron density measurement by the method of Faraday rotation and method for compensating these errors
Keywords: радар некогерентного рассеяния; эффект Фарадея; поляризационный эллипс; способ компенсации ошибок; incoherent scatter radar; electron density; Faraday Effect; polarization ellipse; measuring errors; technique for error compensation